How to raise career aspirations in farming via digital media: A closer look at social media savvy urban farmers - Ilkay Unay-Gailhard; Robert J. Chaski; Mark A. Brennan (Urban Agriculture Magazine, 2024)
Farming is facing a generational renewal problem, with an increasing proportion of farmers near retirement age and a lack of people who are able or willing to take over farms. The low percentage of young farmers in the EU and the US impairs resilience in farming and threatens food security. Findings from a study in the EU and the US identify two main challenges: a global difficulty in attracting youth into farming, and the increasing pressure on institutions to provide efficient knowledge transfer to youth via online platforms.
Keywords: 630